Exposure To Ai Content And The Rationalisation of Digital Privacy Abuse: A Study Among Students at University X in Pekanbaru - Sa’diyah Aristawati Septini; Fakhri Usmita (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The rapid development of generative Artificial Intelligence (AI) has triggered the "photos with idols" Prompt-AI content trend, which manipulates visual identities on social media,. This study aims to measurably analyze the relationship between exposure to such Prompt-AI content and the tendency to neutralize (normalize) digital privacy abuse among students at University X in Pekanbaru. The research employed a quantitative approach with a descriptive design. Data were collected via online questionnaires using a four-point Likert scale from 103 student respondents selected through purposive sampling,. Data analysis was conducted using the Pearson Product Moment correlation test via SPSS software, following validity and reliability confirmation (Cronbach's Alpha > 0.80) and ensuring normal data distribution through the One-Sample Kolmogorov-Smirnov test,. The results demonstrate a significant positive relationship of moderate strength (r=0.535; p=0.000) between content exposure and the neutralization of digital privacy abuse.